GE_GERICHTE PS/77/2019 vom 25. November 2019 - GE Cour de justice (2019)
REFUS DE STATUER;ACTION EN NULLITÉ(EN GÉNÉRAL);SÉQUESTRE(MESURE PROVISIONNELLE);CONFISCATION(DROIT PÉNAL);SOUPÇON;SIGNATURE | LArm.31; CPP.263; LArm.34; LARM.36; CPP.17; RaLArm.3; CPP.80; CPP.353